A Compact UWB Antenna With Dual Band‐Notch Characteristics Using Nested Split Ring Resonator and Stepped Impedance Resonator. Issue 12 (23rd September 2013) - Li, Yingsong; Li, Wenxing; Ye, Qiubo
ABSTRACT In this article, a wide‐slot ultrawideband antenna with dual band‐notch characteristics is proposed numerically and verified experimentally. The dual band‐notch functions are obtained by using a nested split ring resonator (NSRR) and a stepped impedance resonator (SIR). The designed two notch bands are tunable by adjusting the dimension of the NSRR and the SIR. Simulation and measurement results agree well. The proposed antenna with omnidirectional radiation patterns and desired notch bands is suitable for UWB communication applications. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:2827–2830, 2013